Pengaruh Efektivitas PAD, Ketergantugan Keuangan Daerah, dan Efisiensi Keuangan Daerah Terhadap Alokasi Belanja Modal Pada Pemerintah Provinsi Se-Sumatera - Riski Ayuni; Kartika Rachma Sari; Eka Jumarni Fithri (Student Research Journal, 2023)
One way to achieve a goal in regional autonomy, especially in terms of improving welfare and community services, is through capital expenditure. This study aims to determine the effect of Financial Performance on the Capital Expenditure Allocation of Provincial Governments in Sumatra for 2017-2021. The population in this study is 10 Provincial Governments with a total observation data (sample) of 50 Provincial Government APBD Realization Reports throughout Sumatra. Testing this hypothesis using multiple linear regression with the help of Eviews 12 software. The results of this study show that partially the Effectiveness of PAD and Regional Financial Efficiency have a significant negative effect on Capital Expenditure Allocation. Meanwhile, Regional Financial Dependence does not have a significant effect on Capital Expenditure Allocation.